The U-Shaped Effects of Financial Leverage and Firm Size on Cash Holding in Indonesia - Iswadi Bensaadi (Journal of Economics, Business, and Accountancy Ventura, 2025)
This study examines the impact of financial leverage and firm size on cash holdings in Indonesia and explores how these effects differ before and during the COVID-19 crisis. The research utilizes unbalanced panel data, comprising 209 firm-year observations from 2018 to 2020. The findings reveal that financial leverage and firm size exhibit a U-shaped relationship with cash holdings. Specifically, in companies with low finan-cial leverage and small firm size, both financial leverage and firm size negatively affect cash holdings. Conversely, in companies with high financial leverage and large firm size, these factors positively influence cash holdings. The study also finds that financial leverage, regardless of whether it is low or high, has a consistent effect on cash hold-ings across the pre- and during-COVID-19 periods. However, the impact of firm size on cash holdings differs between small and large companies when comparing the pre-COVID-19 and during-COVID-19 periods. This research contributes to the literature on cash holdings by analyzing the U-shaped effects of financial leverage and firm size in manufacturing companies in Indonesia, employing a static random effects model.